Fatigue and tribological properties of plastics and elastomers. (Plastics Design Library, 1995)
This handbook is a database reference covering fatigue behavior and friction and wear characteristics of 106 plastics and elastomers. Data presented details the differences in behavior between generic families of plastic and rubber materials. Also covered are differences within the same generic family due to factors such as temperature, test frequency, and mating surface details (in the case of tribological properties) or material characteristics, such as sample preparation and material composition. Also covered are the tribological (friction and wear) properties of plastics and elastomers. Tribological information is presented as combinations of text, graphs, and tables. Textual data are presented as concise discussions of topics relating to the friction and wear behavior of the material of interest. Graphs show how variables affect the friction and wear properties. Tables cover coefficient of friction data, wear factor (K), wear rate, PV Limits, and abrasion resistance data.
Keywords: Plastics -- Fatigue -- Charts, diagrams, etc.; Elastomers -- Fatigue -- Charts, diagrams, etc.; Tribology.; elektronické knihy; electronic books